PENGARUH HARGA DAN KUALITAS PRODUK SERTA CITRA MEREK TERHADAP PENGAMBILAN KEPUTUSAN PEMBELIAN SEPATU NIKE DI KOMUNITAS EROS BASKETBALL KOTA SAMARINDA - Muhammad Khairon; Saida Zainurrosalamia Za (Jurnal Ekonomi, Manajemen dan Akuntansi, 2025)
This study aims to examine the influence of price, product quality, and brand image on purchasing decisions for Nike shoes among members of the Eros Basketball community in Samarinda City. Nike was selected due to its strong brand presence and popularity among athletes and sports enthusiasts. The population of this research consists of active members of the Eros Basketball community, with a sample size of 100 respondents. A quantitative approach was employed, using survey methods via a questionnaire distributed online through Google Form. The collected data were analyzed using the latest version of SPSS to determine the significance of the relationship between independent variables and the dependent variable purchase decisions. The analysis results reveal that product quality has a significant and positive impact on purchasing decisions. This highlights the importance of comfort, durability, and design in attracting consumers. In contrast, price does not have a significant influence, indicating that community members tend to prioritize product quality over cost when making purchase decisions. Moreover, brand image also shows a significant effect, suggesting that the perception of Nike’s excellence, reputation, and symbolic value strongly contributes to consumer decision-making processes.